Quality-Based School Work Program Training at SDIT Ar Ruhul Jadid Jombang - Suwandi; Erika Mei Budiarti; Lukman Hakim; Abdullah Aminuddin Aziz; Asep Kurniawan (Journal of Research and Community Service, 2025)
The quality of basic education is strongly influenced by the effectiveness of school work program planning that is systematic, measurable, and aligned with quality standards. In practice, however, many Integrated Islamic Elementary Schools (Sekolah Dasar Islam Terpadu/SDIT) still face limitations in developing annual school work programs that are fully integrated with the National Education Standards and principles of quality management. This community service activity aimed to strengthen school management capacity in developing quality-based school work programs through structured training and mentoring at SDIT Ar Ruhul Jadid Jombang. The activity employed a participatory and contextual approach, implemented through interactive workshops and intensive technical mentoring involving the principal, teachers, and educational staff. Data were collected using pre-tests and post-tests, direct observation, document analysis, and participant response questionnaires. The results indicate a significant improvement in participants’ conceptual understanding of education quality, Total Quality Management, and the National Education Standards, as reflected in the increase of the average score from 58.7 in the pre-test to 85.2 in the post-test. In addition, participants demonstrated enhanced technical skills in formulating school work programs that are more systematic, measurable, and aligned with quality indicators. The main output of this activity was a draft of a quality-based annual school work program that is ready for implementation. The findings imply that structured training and mentoring can effectively strengthen a school’s quality culture and managerial effectiveness, while also offering a practical and replicable model of community service for improving quality-oriented school management in Integrated Islamic Elementary Schools.